Pengaruh Variasi Jenis Katalisator Dan Holding Time Pada Proses Pack Carburizing Terhadap Perubahan Komposisi Karbon Dan Nilai Kekerasan Baja Karbon Rendah (Low Carbon Steel) St 37 - Dwi Handoko; Vivaldi Vivaldi; Sutrisno Sutrisno (Vokasi, 2021)
In this study, a pack carburizing process was carried out on low carbon steel using activated carbon, coconut shell charcoal and various catalysts in the form of ale-ale shells, eggshells, and beef bones. The method used is heating at an austenite temperature of 900 oC with a variation of holding time of 30, 60, and 90 minutes, then quenching using water, followed by hardness testing with the Vickers method and composition testing. The general result is that the three types of catalysts can accelerate the diffusion-reaction so that the carbon addition process occurs and the longer holding time can provide an opportunity for the carbon formed to transform from the pearlite microstructure to the austenite microstructure, and when quenching it forms the Martensite microstructure. Of the three types of catalysts that produced the highest hardness was an ale-ale shell, from the initial hardness 119 HV to 464 HV.